2009
DOI: 10.1128/iai.00558-09
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment of Clostridium difficile Carrier Mice Triggers a Supershedder State, Spore-Mediated Transmission, and Severe Disease in Immunocompromised Hosts

Abstract: Clostridium difficile persists in hospitals by exploiting an infection cycle that is dependent on humans shedding highly resistant and infectious spores. Here we show that human virulent C. difficile can asymptomatically colonize the intestines of immunocompetent mice, establishing a carrier state that persists for many months. C. difficile carrier mice consistently shed low levels of spores but, surprisingly, do not transmit infection to cohabiting mice. However, antibiotic treatment of carriers triggers a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
338
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(363 citation statements)
references
References 66 publications
13
338
3
2
Order By: Relevance
“…Several studies of transmission in animal hosts have also shown a scaling of transmission fitness with pathogen load, e.g. Salmonella and Clostridium difficile transmission in mice [61,62] and Escherichia coli in cattle [63]. All these examples suggest that for some diseases and under some scenarios, infectiousness might be directly determined by pathogen load.…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…Several studies of transmission in animal hosts have also shown a scaling of transmission fitness with pathogen load, e.g. Salmonella and Clostridium difficile transmission in mice [61,62] and Escherichia coli in cattle [63]. All these examples suggest that for some diseases and under some scenarios, infectiousness might be directly determined by pathogen load.…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…22 In some cases this can lead to the development of colitis. 23,24 In this present study, we utilized antibiotic-treated mice to demonstrate that altering the community structure of the indigenous gut microbiota is associated with both the loss of colonization resistance against C. difficile and differences in the severity of disease.…”
Section: The Interplay Between Microbiome Dynamics and Pathogen Dynammentioning
confidence: 99%
“…The mouse model is well established to study colonisation but has recently also been developed as an infection model. 29 The piglet model has also been described as mimicking CDI well. 30 Throughout these studies, it should be borne in mind that while extremely useful, animals are only a model of human disease.…”
Section: The Relative Roles Of Toxin a And Bmentioning
confidence: 99%